1998
DOI: 10.1111/j.1745-4506.1998.tb00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality Grade, Portion Size, Needle Tenderization and Cookery Method Effects on Cooking Characteristics and Palatability Traits of Portioned Strip Loin and Top Sirloin Steaks

Abstract: Strip Loin (IMP # 1180A) and Top Sirloin Center Cut steaks (IMP # 1184B) purchased from a foodservice purveyor and aged 21 days were used to evaluate cookery method, needle tenderization, quality grade and portion size effects on palatability and cooking characteristics. Both steak types were distributed across 4 quality grade classes (USDA Select = S, USDA Choice = C, USDA Prime = P, and Certified Angus BeefTM= UC), 2 portion sizes (strip loins, 283 and 397 g; top sirloins, 255 and 340 g), 2 tenderization tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…The CS cookery method reduced cooking time by about 60% (P < 0.05) compared to FB cooked chops. This is similar to results from Berry and Leddy (1990), Berry (1993), Berry and Bigner (1995), Gardner et al (1996), and Pringle et al (1998) using beef steaks. Results from this study showed CS cooked chops had numerically lower shear force values than FB cooked chops, however, these differences were not significant.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The CS cookery method reduced cooking time by about 60% (P < 0.05) compared to FB cooked chops. This is similar to results from Berry and Leddy (1990), Berry (1993), Berry and Bigner (1995), Gardner et al (1996), and Pringle et al (1998) using beef steaks. Results from this study showed CS cooked chops had numerically lower shear force values than FB cooked chops, however, these differences were not significant.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the smaller portion sized pork chops had lower (P < 0.05) cooking losses, which may be due to the fact that these chops had significantly shorter cook times than the larger portion size. Pringle et al (1998) documented similar results in portioned beef loin steaks.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations